2007
DOI: 10.1002/j.2168-9830.2007.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

K‐12 Outreach: Identifying the Broader Impacts of Four Outreach Projects

Abstract: Over the last four years, a series of outreach programs have been offered through the Colorado School of Mines to middle school teachers from eleven school districts in the State of Colorado in the United States. Each of these programs is designed to illustrate through hands‐on activities the application of mathematics to science and engineering. Each also has an academic year follow‐up such that a faculty member, an expert teacher, or a graduate student assists the teachers in the classroom. An expected outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…16 One approach that has been used successfully to increase student interest and awareness in STEM is improving the education of both students and teachers through personal contact with practicing STEM professionals. 17,18 From an academic and industrial perspective, this is known as "educational outreach. "…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 One approach that has been used successfully to increase student interest and awareness in STEM is improving the education of both students and teachers through personal contact with practicing STEM professionals. 17,18 From an academic and industrial perspective, this is known as "educational outreach. "…”
Section: Introductionmentioning
confidence: 99%
“…18 A series of programs involved intensive summer teacher training programs along with in-class follow-up and support over the course of the subsequent academic year. Faculty and graduate teaching fellows assisted the teachers with the incorporation of active learning in their lesson plans.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers recommend introducing engineering in the context of math and science at earlier ages to increase interest and the most direct route to improve math and science achievement is undoubtedly better teaching [3,19]. Teachers need to learn what to teach and how to teach it [20]. As a result, there is a large movement to provide professional development opportunities for in-service teachers to help integrate engineering content [18].…”
Section: Outreach Programsmentioning
confidence: 99%
“…Jeffers et al [3] states, "The key is to have informed and motivated teachers that can excite and instill confidence in their students." Professional development opportunities should introduce techniques for integrating content within the curriculum [6,20] and teachers should have an opportunity to experience what they will have their students do [13]. Best practices show that teacher workshops followed by student camps are the most effective sequences for teacher development.…”
Section: Outreach Programsmentioning
confidence: 99%
“…4 From the university side, research has found these activities to improve the experiences of the graduate students who frequently apply newly developed curricula and to inspire graduate students to maintain a K-12 connection after they graduate. 5 …”
Section: Outreach In Stem Fieldsmentioning
confidence: 99%